Survei Tingkat VO₂max Pada Siswa Kelas VIII Peserta Ekstrakurikuler Sepak Bola SMP Ar Raudloh Karangtanjung Kebumen - Wahibul Hidayat; Khafid Ikhram (Jurnal Kridatama Sains dan Teknologi, 2026)
This research was motivated by an observed pattern of stamina decline among eighth-grade students participating in the football extracurricular program at SMP Ar Raudloh Karangtanjung Kebumen, particularly during the second half of matches, a pattern that had not previously been supported by objective measurement data. This study aimed to determine students' VO₂max levels based on Bleep Test results and to describe the distribution of their aerobic fitness categories according to established VO₂max norms. This research employed a quantitative descriptive method using a survey approach. The research subjects consisted of 18 eighth-grade students participating in the football extracurricular program at SMP Ar Raudloh Karangtanjung Kebumen, selected through a total sampling technique. Data collection was conducted using the Bleep Test (Multistage Fitness Test) on the school's football field during the odd semester of the 2025/2026 academic year. Test results were converted to VO₂max values (ml/kg/min) using a standard conversion table and subsequently categorized according to Cooper's norms for males aged 13–19 years. Data were analyzed using descriptive statistics, including frequency distribution and percentage. The results showed that students' VO₂max levels ranged from 33.5 to 47.9 ml/kg/min, with a mean value of 40.43 ml/kg/min, which falls into the Fair category according to Cooper's norms. The distribution of aerobic fitness categories was as follows: Fair, 8 students (44.44%); Poor, 5 students (27.78%); Good, 3 students (16.67%); Very Poor, 2 students (11.11%); while no students fell into the Excellent or Superior (Athlete) categories (0.00%). Overall, 83.33% of students were classified below the good category, indicating that most students' cardiorespiratory endurance remains suboptimal for supporting optimal and competitive football performance. These findings underscore the need to evaluate and improve the aerobic endurance training program within the football extracurricular activities at SMP Ar Raudloh Karangtanjung, Kebumen